Evaluation of cellulosic pulps treated by hornification as reinforcement of cementitious composites. (15th December 2015) - Ballesteros, Julian Eduardo Mejia; Santos, Sergio Francisco; Mármol, Gonzalo; Savastano, Holmer; Fiorelli, Juliano
Highlights: Hornification treatment does not deteriorate the fiber quality. Hornificated pulps show good behavior as reinforcement for composites at early ages. Hornification process presents potential to be used as a treatment for cellulosic pulps. Abstract: This study evaluated the effect of the hornification process on cellulosic fibers of bleached pine and unbleached eucalyptus with in order to improve its durability and volume stability to be used as reinforcement in cementitious matrices. The study indicated that the treatment did not deteriorate the properties of viscosity and index of crystallinity and decreased the capacity of water retention. Composites reinforced with hornificated and untreated pulps with thermal curing or accelerated aging were produced and evaluated to assess their physical and mechanical behavior. The use of hornificated fibers as reinforcement generated improvements in the modulus of rupture and specific energy of the composites.